Quality of Building Information System Services in the Management of Building of Merauke Regency - Nenden Siti Khodijah; Yohanis E. Teturan (Indonesian Association for Public Administration (IAPA), 2021)
An observation was made when a new website was launched through the ministry in order to improve the service quality of the Building Information System in the Management of Building Permits (SIMBG) at the One-Stop Integrated Service and Investment Service of Merauke Regency which consists of five quality dimensions, namely: tangibility, reliability, responsiveness, assurance, and empathy. The purpose of this research is to describe the service quality of the Building Information System (SIMBG) in making Building Permits at One-Stop Integrated Service and Investment Service. The research is a descriptive with a qualitative analysis approach in its method. The data collection techniques are: theoretical studies and field studies consisting of observations and interviews. 10 informants were interviewed in the study. They are five informants of IMB officers at DPMPTSP and five informants from the community who have made IMBs online. There are 3 data analysis techniques used, namely data reduction, data presentation, and drawing conclusions/verification. The conclusion of this study illustrates that the use of the 5 dimensions of Parasuraman has met the standards of SIMBG Service Quality at DPMPTSP Merauke Regency in the management of IMB. However, there are some shortcomings and things that have not been met, such as the length of time the applicant data upload process takes, the appropriate length of time for issuance, and coordination with each sub district in Merauke Regency regarding more intensive socialization of online licensing at the Merauke Regency DPMPTSP. Apart from that, it has shown that in general the quality of service is quite optimal in providing public services regarding existing permits in Merauke Regency.